Konsep dan Penerapan Motivasi Dalam Belajar - Amirah, Nadiratul; Nirwana, Herman ,; N, Neviyarni (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Motivation plays a central role in the learning process as the main driver for students to achieve educational goals. This article discusses the concept of motivation, the factors that influence it, and the application of various motivation theories, such as Maslow’s theory of needs, behaviorist theory, dissonance theory, personality theory, attribution theory, expectancy theory, and achievement motivation theory. In addition, the differences between intrinsic and extrinsic motivation are also discussed, as well as the roles of both in supporting learning success. By understanding motivation, teachers can design more effective learning strategies, increase student interest, and optimize learning outcomes. This study uses a literature study method to provide a comprehensive understanding of motivation in learning.